PEMANFAATAN GETAH DAMAR OLEH MASYARAKAT DI KELURAHAN KEDAMIN HULU KECAMATAN PUTUSSIBAU SELATAN KABUPATEN KAPUAS HULU - Arianti, Della Oktavia; Idham, M; Zainal, Sofyan (Universitas Tanjungpura, 2018)
One of the HHBK is sap from resin wood. See its abundant potential in Indonesia resin gum made one of the forest plants that are able to provide production both wood and other results (not wood). Resin is one of the long-know non-timber forest products, producing a sap produced only by certain forest tree species. The aim of this research is to observe the utilization of damar sap by the people of Kedamin Hulu, and also analyzing the relationship between the utilization of damar sap with the level of income, knowledge, and cosmopolitan. This research used descriptive method in form of surveys using interview technique and using questioners as the tool of data collection. Based on the result of the research done to 87 respondents, it is known that from 87 respondents, 3 respondents (4%) have moderate level of utilization, 10 respondents (11%) have low level of utilization. Therefore, it can be concluded that the utilization of damar sap based on the level of utilization tend to have a high-level utilization, from 87 respondent, there are 74 respondents (85%) with high level of utilization. 74 respondents (85%) have positive level of utilization.Keyword: Kapuas Hulu, Non-timber Forest Products, Resin Sap, Resin Wood, Utilization